Recruited and Tissue-Resident Natural Killer Cells in the Lung During Infection and Cancer - Franklin, Miriam; Connolly, Emma; Hussell, Tracy (Frontiers in Immunology, 2022)
Natural killer (NK) cells are an important component of the innate immune system, and have a key role in host defence against infection and in tumour surveillance. Tumours and viruses employ remarkably similar strategies to avoid recognition and killing by NK cells and so much can be learnt by comparing NK cells in these disparate diseases. The lung is a unique tissue environment and immune cells in this organ, including NK cells, exist in a hypofunctional state to prevent activation against innocuous stimuli. Upon infection, rapid NK cell infiltration into the lung occurs, the amplitude of which is determined by the extent of inflammation and damage. Activated NK cells kill infected cells and produce pro-inflammatory cytokines and chemokines to recruit cells of the adaptive immune system. More recent evidence has shown that NK cells also play an additional role in resolution of inflammation. In lung cancer however, NK cell recruitment is impaired and those that are present have reduced functionality. The majority of lung NK cells are circulatory, however, recently a small population of tissue-resident lung NK cells has been described. The specific role of this subset is yet to be determined, but they show similarity to resident memory T cell subsets. Whether resident or recruited, NK cells are important in the control of pulmonary infections, but equally, can drive excessive inflammation if not regulated. In this review we discuss how NK cells are recruited, controlled and retained in the specific environment of the lung in health and disease. Understanding these mechanisms in the context of infection may provide opportunities to promote NK cell recruitment and function in the lung tumour setting.